Application of a 360-Degree Radiation Thermosonication Technology for the Inactivation of Staphylococcus aureus in Milk - Zhou, Jianwei; Sheng, Lele; Lv, Ruiling; Liu, Donghong; Ding, Tian; Liao, Xinyu (Frontiers in Microbiology, 2021)
Milk is easy to be contaminated by microorganisms due to its abundant nutrients. In this study, a 360-degree radiation thermosonication (TS) system was developed and utilized for the inactivation of Staphylococcus aureus in milk. The 360-degree radiation TS system-induced inactivation kinetics of S. aureus was fitted best by Weibull model compared with Biphasic and linear models. The treatment time, the exposure temperature, and the applied ultrasound power was found to affect the bactericidal efficacy of the 360-degree radiation TS system. Additionally, the TS condition of 200 W and 63℃ for 7.5 min was successfully applied to achieve a complete microbial inactivation (under the LOD value) in raw milk. The treatment of 360-degree radiation TS can enhance the zeta potential and decrease the average particle size of milk, as well as it also exhibited better retainment of the proteins in milk compared with the ultrahigh temperature (UHT) and conventional pasteurization processing. Therefore, the 360-degree radiation TS system developed in this study can be used as alternative technology to assure the microbiological safety and retain the quality of milk and and the Weibull model could be applied for the prediction of the inactivation levels after exposure to this technology.